Uzbek terminology; Problems and solutions (Eurasian Journal of Humanities and Social Sciences, 2022)
Technical necessity and need lead to the development of science. The development of branches of science, the emergence of new branches and directions of science, of course, will lead to the improvement of the existing system of terms, the emergence of new terms. This, in turn, leads to the emergence of new problems, issues and tasks in linguistics.